2013
DOI: 10.1089/neu.2012.2584
|View full text |Cite
|
Sign up to set email alerts
|

Safety and Efficacy of Early Pharmacological Thromboprophylaxis in Traumatic Brain Injury: Systematic Review and Meta-Analysis

Abstract: Patients with traumatic brain injury (TBI) are at an increased risk of developing venous thromboembolic events (VTE). Pharmacological thromboprophylaxis (PTP) is routinely delayed because of concerns of exacerbating intracranial hemorrhage (ICH). The aim of this review is to examine the literature and assimilate suitable data to assess the safety and efficacy of PTP administered within 72 h in TBI patients. We systematically searched the literature for randomized controlled trials or cohort studies reporting o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
30
1
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(32 citation statements)
references
References 42 publications
0
30
1
1
Order By: Relevance
“…A meta-analysis by the Brain Trauma Foundation in 2007 showed that there was insufficient evidence to guide the timing of PTP administration in TBI patients [12]. A recent meta-analysis was performed on randomized controlled trials or cohort studies that reported on the timing of PTP in TBI [13]. They also dichotomized the timing of PTP to early and late at 72 h post-injury.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…A meta-analysis by the Brain Trauma Foundation in 2007 showed that there was insufficient evidence to guide the timing of PTP administration in TBI patients [12]. A recent meta-analysis was performed on randomized controlled trials or cohort studies that reported on the timing of PTP in TBI [13]. They also dichotomized the timing of PTP to early and late at 72 h post-injury.…”
Section: Discussionmentioning
confidence: 99%
“…Assessing safety, the relative risk of ICH progression in the early compared with the late PTP group was 0.64 (0.35, 1.14) [13]. If we add the number of patients from our study to the patients in the meta-analysis by Jamjoom and Jamjoom [13], this will add to 51 VTEs (6.4%) in 793 total patients in the < 72 h group versus 119 VTEs (12.4%) in 959 total patients in the > 72 h group.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[5678] Heparin derivatives (such as unfractionated heparin [UFH] or low molecular weight heparin [LMWH]) are often administered subcutaneously as prophylactic treatment when considered safe in the injured patient. [9] However, clinicians caring for patients with brain injury may be hesitant to administer these agents early after injury given the perceived risk of worsening intracranial hemorrhage. [1011]…”
Section: Introductionmentioning
confidence: 99%
“…[11] Meta-analyses based on few studies with the abovementioned limitations, demonstrate that the use of unfractioned (UFH) or low molecular weights heparins (LMWHs) in the acute phase of spontaneous intracranial bleeding significantly reduce the risk of pulmonary embolism (PE) and overall mortality and nonsignificantly reduce the risk of deep vein thrombosis (DVT) without a significant increasing of hematoma enlargement or rebleeding, whereas the early administration of pharmacological prophylaxis in traumatic intracranial hemorrhage within 72 h from bleeding onset significantly reduce the risk of PE, DVT, and overall mortality without increasing the hematoma progression. [1213] The most recent available guidelines recommend to start the pharmacological prophylaxis of VTE in immobilized patients with STBI or ICH by using UFH or LMWHs after 48-72 h from bleeding onset and anyway when clinical and neuroradiological examination is stable. [1415]…”
mentioning
confidence: 99%